2016
DOI: 10.1097/scs.0000000000002729
|View full text |Cite
|
Sign up to set email alerts
|

Premaxillary Repositioning in the Severe Form of Bilateral Cleft Lip and Palate

Abstract: Severe forms of bilateral cleft lip and palate remain a challenging issue. Although nasoalveolar molding dramatically improves overall treatment success, the position of the premaxilla often remains dislocated. The authors attempted to relocate the malpositioned premaxilla into the correct position to obtain the correct three-dimensional (3D) maxillary arch structure and growth. Eight patients with severe bilateral cleft lip and palate were treated with premaxillary osteotomy for premaxilla repositioning. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…Improvements in the position of the premaxilla provided better functioning and aesthetics to the patient, as the premaxilla becomes positioned normally, the superior incisors have better pro-inclination and intrusion, and the overbite is improved; overall, this facilitates later orthodontic movements. These results are similar to those reported by Kyung, et al (2016), who found that premaxillary repositioning effectively corrects a malpositioned premaxilla, achieving a successful restoration of maxillary arch coordination [17].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Improvements in the position of the premaxilla provided better functioning and aesthetics to the patient, as the premaxilla becomes positioned normally, the superior incisors have better pro-inclination and intrusion, and the overbite is improved; overall, this facilitates later orthodontic movements. These results are similar to those reported by Kyung, et al (2016), who found that premaxillary repositioning effectively corrects a malpositioned premaxilla, achieving a successful restoration of maxillary arch coordination [17].…”
Section: Discussionsupporting
confidence: 91%
“…Premaxillary osteotomy is a potentially good solution for severe forms of BCLP [17], as it is not possible to correct BCLP with orthodontics in these severe cases. There are few studies that quantify which patients need osteotomy and which patients do not, as differences in treatment protocols make comparison dif icult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the premaxillary osteotomy is thought to be contraindicated in growing children. Despite the debate, recent publications agree that it could be accepted as a viable alternative for the repair of severe forms of bilateral alveolar cleft (El-Kassaby et al, 2013; Steinhäuser, 2014; Koh et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, surgical repositioning is controversial, with different authors reporting the negative influence on the development of the midface. However, a recently published study has concluded that in children older than 8 years it does not seem to cause significant maxillary retrusion (Koh et al, 2016).…”
Section: Introductionmentioning
confidence: 99%